Trends in the Percentage of Doses of Modified Live, Killed, and Combination Respiratory Viral Vaccines Administered to Beef Calves Offered for Sale in Summer Video Auctions From 2000 Through 2018 - M. J. Smith; K. E. Fike; M. E. King; E. D. McCabe; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective of the study was to identify trends in the percentage of doses of modified live, killed, and combination respiratory viral vaccines administered to lots of beef calves. Study Description:Nineteen years of data (2000–2018) from a livestock video auction service (Superior Livestock Auction, Fort Worth, TX) were analyzed to quantify trends in percentage of doses of respiratory viral vaccine administered to beef calves. Named respiratory viral vaccines were classified into three groups based on the antigens they contained: all modified live antigens, all killed antigens, and combination of modified live and killed antigens. The Cochran-Armitage Trend Test determined presence of a trend in usage of each type. Results:There was an increase (P<0.05) in the number of modified live viral vaccine doses given to beef calf lots from 2000 (41.7%, 121,976 doses) through 2018 (90.3%, 673,862 doses). The trend in the number of doses of both killed and combination viral vaccines administered to beef calves declined (P<0.05) from 2000 through 2018. In 2000, 31.2% (91,176 doses) and 27.1% (79,225 doses) of the total respiratory viral vaccines given to beef calf lots were killed or combination vaccines, respectively. By 2018, only 4.2% (31,325 doses) of respiratory viral vaccines were killed, and only 5.5% (41,136 doses) were combination. The Bottom Line:This dramatic shift indicates an industry trend towards increasing modified live viral vaccine utilization compared with declining usage of killed and combination respiratory viral vaccines. This trend may be a result of modified live viral vaccine approval for use in suckling calves nursing pregnant cows.
Keywords: respiratory viral vaccines; calf health; beef calves